Digital Communication Patterns Of Milenial Extensions And Farmers In Yogyakarta (DIY) Post Pandemi Covid-19 - Tutiasri, Ririn; Kusumajanti; Aulia Rahmawati; Syafrida Nurrachmi Febriyanti; Dian Hutami Rahmawati (LPPM Stikosa - AWS, 2023)
This study examines the communication patterns made by agricultural extension agents for the Special Region of Yogyakarta (DIY) with millennial farmers after the Covid-19 pandemic. The Covid-19 outbreak has changed the way we communicate, especially the use of communication media. A very real change can be seen by keeping a distance when carrying out communications and activities. Everyone is forced by circumstances to be able to use communication media, namely gadgets as a communication tool. The words of millennial farmers started to be heard at the start of the pandemic, where these members of the millennial farmers were different from previous farmers, namely farmers who were media literate and able to adapt quickly to circumstances. Many social media applications are used to communicate during the pandemic, and these millennial farmers choose applications that easily facilitate their communication. Collecting data in this study using interviews, observation, documentation, and focus group discussion (FGD). Data analysis techniques used with qualitative descriptions. Research informants consisted of extension workers and millennial farmers from four districts and one city, namely Kulonprogo, Bantul, Gunung Kidul, Sleman, and Yogyakarta City. The results of the study indicate that there has been a change in communication patterns carried out by extension agents with millennial farmers after the pandemic, due to the use of technology. After the Covid-19 pandemic, information was digitized for farmer groups, they used information technology to communicate. The pattern of farmer communication during the post-pandemic period has also changed, where millennial farmers have taken a role in coordinating information